Torus-connected cycles: A simple and scalable topology for interconnection networks - Bossard, Antoine; Kaneko, Keiichi (Zielona Góra: Uniwersytet Zielonogórski)
Supercomputers are today made up of hundreds of thousands of nodes. The interconnection network is responsible for connecting all these nodes to each other. Different interconnection networks have been proposed; high performance topologies have been introduced as a replacement for the conventional topologies of recent decades. A high order, a low degree and a small diameter are the usual properties aimed for by such topologies. However, this is not sufficient to lead to actual hardware implementations. Network scalability and topology simplicity are two critical parameters, and they are two of the reasons why modern supercomputers are often based on torus interconnection networks (e.g., Fujitsu K, IBM Sequoia).
Keywords: algorithm; routing; Hamiltonian; supercomputer; parallel